Child-Friendly School Program Fosters Students' Psychological Well-Being In Elementary Education: Program Sekolah Ramah Anak Menumbuhkan Kesejahteraan Psikologis Siswa Pada Pendidikan Dasar - Sri Kuntifa; Ari Metalin Ika Puspita; Moch Nursalim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Schools function as formal educational institutions that are responsible for fostering both academic development and the psychological well-being of young learners. Specific Background Despite this mandate, increasing incidents of bullying, excessive academic pressure, and emotional distress continually threaten the psychological security of elementary students. Knowledge Gap Although the Indonesian government mandated the Child-Friendly School Program to combat these issues, empirical qualitative research examining its direct role in cultivating the specific cognitive and affective dimensions of subjective well-being within real-world elementary settings remains limited. Aims This study describes the role of the Child-Friendly School Program on students’ psychological well-being at SDN Putat Jaya IV/380 Surabaya. Results Utilizing a qualitative case study approach with data from principals, teachers, students, and parents, the analysis revealed that the program effectively minimized negative emotional affect, such as fear and anxiety. Concurrently, it promoted positive affect and life satisfaction by fostering secure learning environments, eliminating physical punishments, and nurturing emotionally supportive teacher-student relationships. Novelty This research distinctly bridges Urie Bronfenbrenner's ecological systems theory with Ed Diener's subjective well-being framework, demonstrating that structured non-discriminatory institutional policies directly translate into measurable improvements in childhood emotional security and self-confidence. Implications Educational institutions must systematically enforce non-discriminatory disciplinary policies and prioritize empathetic teacher-student communication to sustain a secure psychological climate that optimizes childhood learning experiences. Highlights The Child-Friendly School Program effectively eliminates fear and anxiety by strictly prohibiting physical disciplinary actions. Emotionally supportive teacher-student interactions directly cultivate positive affective experiences and enhance childhood self-confidence. Structured non-discriminatory institutional policies significantly improve the overall subjective well-being of elementary learners. Keywords Child Friendly School; Psychological Well-Being; Subjective Well-Being; Elementary Education; Learning Environment